Evaluation of somatic and functional parameters of cardiovascular and respiratory systems in rural women in Poland - Ignasiak, Tomasz; Ignasiak, Zofia; Ziółkowska-Łajp, Ewa; Rożek, Krystyna; Sławińska, Teresa; Skrzek, Anna (Anthropological Review, 2012)
The aim of this study was the diagnosis of selected somatic parameters and functional parameters of cardiovascular and respiratory systems of rural women in Poland. The study involved a group of 95 rural women aged 35–60 years, staying in 3-week rehabilitation camps. The two groups of women were selected: younger (x=43 years), which did not exceed 50 years of age (n=48) and older (x=53 years) aged 50 years and older (n=47). The present study examines the measurement of the body height and weight, Body Mass Index (BMI) and functional parameters of cardiovascular and respiratory systems. For the evaluation of cardiovascular parameters, a 6 minute walk test was selected. Before the commencement of the test and in the first minute after it, the pulse and the blood pressure were measured. To assess the functional parameters of the respiratory system, the pattern of flow – volume curve was used. The test was performed with a Jaeger Flowscreen spirometer. The following parameters were determined: forced vital capacity (FVC), forced expiratory volume in one second (FEV1), peak expiratory flow (PEF) and Tiffeneau index (FEV1 in% VC). Examined rural women were likely to be similar to their urban counterparts. BMI of women was significantly higher than peers. Older rural women are particularly at risk of obesity. Heart rate and blood pressure, when at resting and after exercise, were normal and alike in both in young and older women. As expected, younger women had significantly higher levels of respiratory parameters. PEF values in younger women were slightly below the normal limit, and in their older peers, this value was significantly below the normal limit.